The biological effects of the hypolipidaemic drug probucol microcapsules fed daily for 4 weeks, to an insulin-resistant mouse model: potential hypoglycaemic and anti-inflammatory effects - Mooranian, Armin; Negrulj, Rebecca; Takechi, Ryu; Mamo, John; Al-Sallami, H.; Al-Salami, Hani (Springer, 2018)
Probucol (PB) is an hypolipidaemic drug with potential antidiabetic effects. We showed recently using in vitro studies that when PB was incorporated with stabilising lipophilic bile acids and microencapsulated using the polymer sodium alginate, the microcapsules showed good stability but poor and irregular PB release. This suggests that PB microcapsules may exhibit better release profile and hence better absorption, if more hydrophilic bile acids were used, such as ursodeoxycholic acid (UDCA). Accordingly, this study aimed to produce PB-UDCA microcapsules and examine PB absorption and antidiabetic effects in our mouse-model of insulin-resistance and diabetes (fed high-fat diet; HFD). The study also aimed to examine the effects of the microcapsules on the bile acid profile. Healthy mice (fed low-fat diet; LFD) were used as control. Seventy mice were randomly allocated into seven equal groups: LFD, HFD given empty microcapsules, HFD given metformin (M), HFD given standard-dose probucol (PB-SD), HFD given high-dose probucol (PB-H), HFD given UDCA microcapsules and HFD given PB-UDCA microcapsules. Blood glucose (BG), inflammatory biomarkers (TNF-a, IFN-?, IL-1ß, IL-6, IL-10, IL-12 and IL-17), plasma cholesterol, non-esterified fatty acids and triglycerides were analysed together with plasma bile acid and probucol concentrations. PB-UDCA microcapsules reduced BG in HFD mice, but did not reduce inflammation or improve lipid profile, compared with positive control (HFD) group. Although PB-UDCA microcapsules did not exert hypolipidaemic or antiinflammatory effects, they resulted in significant hypoglycaemic effects in a mouse model of insulin resistance, which suggests potential applications in insulin-resistance and glucose haemostasis.